Igniting Students' Passion for Mathematics: The Validity and Realibility of Instrument of Disposition Mathematics - Nadya Dewinda Agustin; Syiti Mutia Hasnan; Edwita; Durotul Yatimah; M. Syarif Sumantri; Arita Marini (LPPM Undiksha, 2025)
This research is motivated by the need for a valid and reliable instrument to measure the mathematical disposition of elementary school students in Indonesia, which includes students' views, emotions, and attitudes towards mathematics and learning as a whole. The main purpose of this study is to develop and test the validity and reliability of questionnaire instruments that can be used by educators in evaluating student characteristics in learning mathematics. This study uses a development research method with a 4D model (Define, Design, Develop, and Disseminate) that has been adapted. The research subjects consisted of elementary school students in Indonesia. Data was collected through the distribution of developed questionnaires, then analyzed using validity and reliability tests. Item validity was tested by correlation analysis, while instrument reliability was analyzed using Cronbach's Alpha. The results showed that the developed instrument had high reliability, although there were some invalid items that needed to be revised. In conclusion, this instrument is considered valid, reliable, and practical to be used to evaluate students' mathematical dispositions. The implication of this study is that the instrument developed can help educators in designing more effective mathematics learning strategies based on the characteristics of student disposition.